Report: Handbook for ICT projects for Rural Areas - Fitri Suraya, Mohamad (2017)
This presentation talks about the completion of an assigned APT Publication grant, to document and illustrate knowledge and experiences accumulated over the past decade by research teams across South East Asia, to design and implement ICT projects in rural areas.